Book Reviews - Berglund, Carl Johan; Bergström, Ulf; Damgaard, Finn; Eidevall, Göran; Elgvin, Torleif; Eriksson, LarsOlov; Forsling, Josef; Hägerland, Tobias; Imberg, Johannes; Johnson, Bo; et al. (Svensk Exegetisk Årsbok, 2013)
The following books are reviewed: Klaus-Peter Adam, Friedrich Avemarie och Nili Wazana (red.), Law and Narrative in the Bible and in Neighbouring Ancient Cultures (Josef Forsling) Stephen P. Ahearne-Kroll, Paul A. Holloway och James A. Kelhoffer (red.), Women and Gender in Ancient Religions: Interdisciplinary Approaches (Hanna Stenström) Dale C. Allison, Volker Leppin, Choon-Leong Seow, Hermann Spieckermann, Barry Dov Walfish och Eric Ziolkowski (red.), Encyclopedia of the Bible and Its Reception, v. 3 (Göran Eidevall) Dale C. Allison, Volker Leppin, Choon-Leong Seow, Hermann Spieckermann, Barry Dov Walfish och Eric Ziolkowski (red.), Encyclopedia of the Bible and Its Reception, v. 5 (Mikael Larsson) Joseph L. Angel, Otherworldly and Eschatological Priesthood in the Dead Sea Scrolls (Torleif Elgvin) Eve-Marie Becker och Anders Runesson (red.), Mark and Matthew I: Comparative Readings: Understanding the Earliest Gospels in their First-century Settings (Tobias Hägerland) Bob Becking, Ezra, Nehemiah, and the Construction of Early Jewish Identity (Lena-Sofia Tiemeyer) April D. DeConick, Holy Misogyny: Why the Sex and Gender Conflicts in the Early Church Still Matter (Hanna Stenström) Daniel R. Driver, Brevard Childs, Biblical Theologian: For the Church’ s One Bible (LarsOlov Eriksson) Göran Eidevall och Blaženka Scheuer (red.), Enigmas and Images: Studies in Honor of Tryggve N. D. Mettinger (Stig Norin) Weston W. Fields, The Dead Sea Scrolls: A Full History (Cecilia Wassén) Miriam Goldstein, Karaite Exegesis in Medieval Jerusalem: The Judeo-Arabic Pentateuch Commentary of Yūsuf ibn Nūḥ and Abū al-Faraj Hārūn (Lena- Sofia Tiemeyer) Leif Hongisto, Experiencing the Apocalypse at the Limits of Alterity (Hanna Stenström) Jan Joosten, The Verbal System of Biblical Hebrew: A New Synthesis Elaborated on the Basis of Classical Prose (Ulf Bergström) Christos Karakolis, Karl-Wilhelm Niebuhr och Sviatoslav Rogalsky (red.), Gospel Images of Jesus Christ in Church Tradition and in Biblical Scholarship (Mikael Sundkvist) Thomas Kazen, Issues of Impurity in Early Judaism (Cecilia Wassén) Chris Keith, Jesus’ Literacy: Scribal Culture and the Teacher from Galilee (Tobias Ålöw) Anthony Le Donne, The Historiographical Jesus: Memory, Typology, and the Son of David (Jennifer Nyström) Kenneth Liljeström (red.), The Early Reception of Paul (Martin Wessbrandt) Aren M. Maeir, Jodi Magness and Lawrence H. Schiffman (ed.), ‘Go Out and Study the Land’ (Judges 18:2): Archaeological, Historical and Textual Studies in Honor of Hanan Eshel (Torleif Elgvin) David L. Mathewson, Verbal Aspect in the Book of Revelation: The Function of Greek Verb Tenses in John’s Apocalypse (Jan H. Nylund) Robert K. McIver, Memory, Jesus, and the Synoptic Gospels (Jennifer Nyström) Sun Myung Lyu, Righteousness in the Book of Proverbs (Bo Johnson) Stefan Nordenson, Genom honom skapades allt: En exegetisk studie om Kristi preexistens och medlarfunktion i Nya testamentet (Hanna Stenström) Stefan Nordgaard Svendsen, Allegory Transformed: The Appropriation of Philonic Hermeneutics in the Letter to the Hebrews (Johannes Imberg) Donna Lee Petter, The Book of Ezekiel and Mesopotamian City Laments (Lena-Sofia Tiemeyer) Stanley E. Porter, Jeffrey T. Reed och Matthew Brook O’Donnell, Fundamentals of New Testament Greek (Jan H. Nylund) Stanley E. Porter och Jeffrey T. Reed, Fundamentals of New Testament Greek: Workbook (Jan H. Nylund) Karl Olav Sandnes, The Gospel ‘According to Homer and Virgil’: Cento and Canon (Maria Sturesson) Tanja Schultheiss, Das Petrusbild im Johannesevangelium (Finn Damgaard) William A. Tooman, Gog of Magog: Reuse of Scripture and Compositional Technique in Ezekiel 38–39 (Lena-Sofia Tiemeyer) Paul Trebilco, Self-designations and Group Identity in the New Testament (Rikard Roitto) Caroline Vander Stichele och Hugh Pyper (red.), Text, Image, and Otherness in Children’s Bibles: What Is in the Picture? (Mikael Larsson) Patricia Walters, The Assumed Authorial Unity of Luke and Acts: A Reassessment of the Evidence (Carl Johan Berglund) Amanda Witmer, Jesus, the Galilean Exorcist: His Exorcisms in Social and Political Context (Jennifer Nyström)